Human trafficking: Tinjauan Viktimologis di Wilayah Sulawesi Tenggara - Rahayu Kojongian; Awaluddin Yasir (Sawerigading Law Journal, 2026)
Human trafficking is a serious crime that constitutes a grave violation of human rights and continues to occur in various regions of Indonesia, including within the jurisdiction of the Southeast Sulawesi Regional Police. This study aims to analyze the causal factors, the role of victims, and the efforts to combat human trafficking from a victimological perspective. The research employs normative legal research combined with an empirical approach, with data collected through interviews and literature review. The findings indicate that cases of human trafficking in Southeast Sulawesi occurred during the 2023–2024 period, with 14 cases recorded in 2023 and 11 cases in 2024. The primary contributing factors include economic hardship, environmental influences, opportunity structures, and low levels of education. From a victimological perspective, victims are positioned as vulnerable individuals due to economic pressure, trust-based social relations, and limited legal literacy, making them highly susceptible to victimization. The study also reveals that victims play a passive role in the occurrence of the crime; however, this should not be interpreted as victim culpability, but rather as an indication of the failure of social and legal protection systems to safeguard vulnerable groups. Efforts to combat human trafficking are carried out through preventive, repressive, and victim protection approaches, including public awareness campaigns, law enforcement actions against perpetrators, and the provision of restitution, rehabilitation, and legal protection for victims. This study emphasizes the importance of a victimological approach in policies addressing human trafficking, ensuring that law enforcement is not solely perpetrator-oriented but also focused on the protection and recovery of victims.